The effect of different warm-up protocols on young soccer players' explosive power - Alikhajeh, Y.; Mohamadi, M. A.; Yaghoubi, M.; Rasekhi, M. J. (Procedia - Social and Behavioral Sciences, 2012)
Objective: To investigating the effect of different Warm-up Protocols on young Soccer Players' Explosive Power. Methods: Twenty male soccer players (17.4 +/- 0.685 years) volunteered to participate in this study. The participants were randomly selected, and in order to remove the effects of transmission and to observe the sequence of warm-up methods, they were cross-matched randomly e.g. 20 players in four categories; that is, 5 players in each category. The participants in each category experienced the 4 warm-up ways in four consecutive so that at the end 20 players performed each method of warm-up.